Pengaruh Menonton Tayangan Beauty Vloger Tasya Farasya Dalam Video Youtobe Terhadap Perilaku Fomo Pembelian Produk Kecantikan Merek Luxcrime Pada Mahasiswa Ilmu Komunikasi UNSIKA Angkatan 2020: Ilmu Komunikasi - Salsabila, Delia; Yuni Dharta, Firdaus; Nurkinan, Nurkinan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the influence of Message Content, Communicator, Effect of watching Tasya Farasya's beauty vlogger show on FOMO behavior in purchasing Luxcrime brand beauty products on communication science students at Singaperbangsa University, Karawang, class of 2020. The theory used is SOR (Stimulus-Organism-Response) by Houland. The method used is quantitative with nonprobability sampling samples with saturated sampling techniques. The number of respondents used in this study was 101 respondents. The analysis used includes descriptive analysis, normality test, simple linear regression test, coefficient of determination, and t-hypothesis test. The results showed that Tasya Farasya's beauty vlogger show in YouTube videos had a positive influence of 16.9% on FOMO behavior in purchasing Luxcrime brand beauty products, while the remaining 83.1% was influenced by other factors.